ANALISIS STRATEGI BERSAING INDUSTRI KECIL MAKANAN TRADISIONAL (KASUS PADA USAHA LEMPUK DURIAN DI KABUPATEN BENGKALIS ) - Kartika Agustina; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted on a small industrial traditional food lempuk durian, Bengkalis regency. The purpose of this study was to analyze the competitive strategy adopted by employers lempuk durian in Bengkalis regency from marketing their products and to find out the constraints faced by entrepreneurs lempuk durian Bengkalis regency.this research used census method by using the tools / techniques of data collection in the form of a structured interview conducted on 15 lempuk durian industry in Bengkalis regency. analysis by the author is a descriptive analysis.From the research, the authors concluded that the competitive strategy applied lempuk durian industry to create competitive advantage with 3 porter generic strategies that cost advantage, differentiation strategy and focus strategy. As well as the efforts made to each of competitive strategy, 1) Efforts to strategy, namely competitive advantage over similar products in terms of the type / shape / size, cost efficiency, and competitive prices. 2) differentiation strategy is through product differentiation, service differentiation, and differentiation image. 3) strategies that focus on serving specific consumer groups, and serve demand orders from certain areas. Constraints faced by the company is a small capital, and seasonal raw materials.Keywords: SMEs (SMALL AND MEDIUM ENTERPRISES), competitive strategy cost advantage, differentiation strategy and focus strategy